The effect of macrophages on the hormone-releasing cells in mouse pituitary - Laine, Elina (My University, 2022)
At the base of the brain is located the pituitary gland which secretes hormones to the bloodstream. Among other cells, the pituitary is resided by macrophages which take part in the immune system by phagocyting pathogens. I studied if macrophages have an impact on the hormone-releasing cells in mouse anterior pituitary and if they share the same intratissue localization. RNAscope® assay was used to evaluate macrophage-specific gene expression in the pituitary of wild-type mice. Then, both hormone-releasing cells and macrophages were studied by immunofluorescence staining. The number of active hormone-releasing cells secreting growth hormone, luteinizing hormone, prolactin and thyroid-stimulating hormone were compared between wild-type and Plvap-/- mice. The knock-out model lacks macrophages derived from the fetal liver. Lastly, pituitary tissue sections from wild-type mice and CCR2-/- and Nur77-/- mice were haematoxylin and eosin stained for histological comparison. Murine CCR2 is involved in macrophage recruitment and Nur77-/- mice do not have Ly6Clow monocytes. The RNAscope® assay appeared not to be the best method to study the targeted genes and so, different macrophage populations could not be identified. Another method might be found to get clear results from the macrophage populations in question. Macrophages could not be detected in the immunofluorescence experiment together with the hormonal cells. However, the results showed that Plvap-/- have less cells secreting growth hormone and luteinizing hormone than wild-type mice, while the number of the other studied hormonal cells were not significantly different between the mouse strains. Earlier hormonal measurements have resulted in low prolactin levels in Plvap-/- pituitary so it is interesting that the number of hormonal cells is not lower in the knock-out pituitaries. Also, both macrophages and the hormone-releasing cells would be beneficial to get detected at the same time. The histological comparison did not show any differences in the pituitary sections of CCR2 and Nur77 knock-outs and wild-type mice. Changes in these two knock-out models do not seem to affect the colonization and the number of the hormone-releasing cells in the pituitary gland. Overall, macrophages originating from the fetal liver seem to affect the secretory cells of growth hormone and luteinizing hormone while the monocyte-derived macrophages do not. More studies focusing on this phenomenon are needed.
Keywords: pituitary gland, anterior lobe, macrophages, hormone-releasing cells, RNAscope, immunofluorescence, haematoxylin and eosin staining, knock-out, mouse, Plvap, CCR2, Nur77, growth hormone, prolactin, luteinizing hormone, thyroid-stimulating hormone